The Analgesic Effect of Intrathecal Dexmedetomidine or Clonidine, with Bupivacaine, in Trauma Patients Undergoing Lower Limb Surgery: A Randomised, Double-Blind Study. Issue 1 (January 2013) - Solanki, S. L.; Bharti, N. A.; Batra, Y. K.; Jain, A.; Kumar, P.; Nikhar, S.
This randomised, double-blind study was designed to compare the duration of analgesia and adverse effects following intrathecal administration of dexmedetomidine or clonidine, both with bupivacaine, in trauma patients. Ninety adult trauma patients of American Society of Anesthesiologists physical status I—II, scheduled for lower limb surgery under subarachnoid block, were randomly allocated to one of three groups. All groups received hyperbaric bupivacaine 0.5% 3 ml, to which was added saline 0.5 ml (Group B): clonidine 50 μg (Group C) or dexmedetomidine 5 μg (Group D). The onset and duration of sensory and motor blockade, severity of postoperative pain, time to first rescue analgesia and total analgesic requirement for 24 hours were noted. There was no significant difference in the onset time of the block but the duration of sensory and motor blockade was prolonged in Groups C and D, compared with Group B. The time to analgesia was significantly prolonged in Group D (824±244 minutes) compared with Group C (678±178 minutes; P =0.01), the latter being longer than Group B (406±119 minutes; P =0.0001). Postoperative pain scores were lower in Groups C and D compared with Group B. The requirement for rescue analgesia during the first 24 postoperative hours was significantly less in Groups C and D as compared to Group B ( P =0.0001), but comparable between Group C and D ( P =0.203). In conclusion, dexmedetomidine 5 μg added to intrathecal bupivacaine 15 mg produces longer postoperative analgesia than clonidine 50 μg among trauma patients undergoing lower limb surgery.